EFFECT OF TEMPERATURE OF BINDING LIQUID ON SOME TABLET PROPERTIES (Biological Sciences - PJSIR, 2001)
The effect of temperature o the granulating fluid on some physical properties of lactose granules and tablets was inves tigated . Checks on granule ize, flow rate and tap density of the granules and hardness, friability and disintegration time at temperatures between 201and 60°C were carried out. Also, temperature effect on the viscosity of the granulating fluids, water and maize starch mucage, was observed. The viscosity of maize starch mucilage was found to decrease as tempera ture increased, while there was no noticeable effect on water. Also, it was found that the granule size increased with temperature up to about 50° after which there was no more increase. The flow rate followed the same pattern, except that there was a decrease beyon 40°C. The tap density was not significantly affected, thus signifying that flow of granules from the hopper to the die i the tabletting machine was not affected equally . The tablet hardness increased as the tem perature decreased from 60 to 25°C while friability showed a reverse. Standardization of the temperature of the granulat ing fluid is therefore essent al.